The Double Challenge of English Teachers: Teaching and Administrative Task - Rahmawati, Amelia Putri; Rakhmawati, Rakhmawati; Fauziana, Erni (ICONELT, 2024)
Teachers, particularly English teachers, face a significant challenge in managing their primary responsibility of teaching with the increasing administrative workload. The findings revealed that the growing administrative tasks, coupled with the integration of technology and the internet, have consumed a substantial amount of time and energy that should have been devoted to instructional preparation. Additionally, the study highlighted the negative impact on teachers’ motivation and job satisfaction, as they felt unable to fully explore students’ needs and preferences regarding teaching styles, leading to monotonous classroom environments. Although some schools have provided specific training to assist teachers in managing administrative workloads more efficiently, there is a need for more comprehensive solutions, such as reducing the overall administrative burden across all subject areas.